(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
English language teaching plays a vital role in shaping students’ perspectives and fostering a sense of patriotism. By incorporating the principles of patriotic education into English language learning, students can develop not only language skills but also a strong sense of love and pride for their country. This article explores how the integration of patriotic education in English language teaching can contribute to students’ holistic development.